Intranasal deferoxamine attenuates synapse loss via up-regulating the P38/HIF-1α pathway on the brain of APP/PS1 transgenic mice - Guo, Chuang; Zhang, Yu-Xin; Wang, Tao; Zhong, Man-Li; Yang, Zhao-Hui; Hao, Li-Juan; Chai, Rui; Zhang, Shuai (Frontiers in Aging Neuroscience, 2015)
Abstract The widely recognized neuroprotective effect of iron chelators is contributed by their ability to prevent reactive oxygen species generation via the Fenton reaction, which sequesters redox-active Fe. An additional neuroprotective mechanism of iron-chelating compounds is to regulate the transcriptional activator hypoxia-inducible factor 1α (HIF-1α). In the present study, we observed that intranasal administration of deferoxamine decreased beta-amyloid (Aβ) deposition and rescued synapse loss in the brain of Aβ precursor protein and presenilin-1 (APP/PS1) double transgenic mice. We found that DFO up-regulated HIF-1α mRNA expression and its protein level, and further induced the proteins that are encoded from HIF-1-adaptive genes, including transferrin receptor (TFR), divalent metal transporter 1 (DMT1), and brain-derived neurotrophic factor (BDNF). The effects of DFO on the induction and stabilization of HIF-1α were further confirmed in vitro. This was accompanied by a decrease of Fe in the CA3 region of the hippocampus. Western blotting studies revealed that DFO differentially enhanced the phosphorylation of mitogen-activated protein kinase (MAPK) /P38 kinase in vitro and in vivo. The results suggest that the DFO may up-regulate several HIF-1-dependent neuroprotective-adaptive genes in AD via activating P38/HIF-1α pathway, which may serve as important therapeutic targets to the disease.